Exploring the possibilities of introducing coffee in the forest based ecosystem of Bastar, Chhattisgarh - Singh, Krishan Pal; Singh, Beena (Indian Horticulture, 2022)
Coffee was introduced in India after Baba Budan carried seven coffee beans from Arabia that are said to have been planted near his hermitage in Dattatreya Peeth presently known as Chikmagalur in Karnataka. India has always been one of the major producers of coffee since ancient times and leads its production representing around 3.5% of the world coffee. Over a 50-year period, coffee has made significant contribution to the Indian economy among the other plantation crops. India is the only country that grows most of its coffee under shade. The Indian coffee is one of the most bizarre beverages in terms of its exotic flavour and aroma. For a sustainable coffee production, the protection of agro-ecosystems especially the forest biomass is a must which can be attained easily by plantingmore trees per unit area. This article explores the possibilities of introducing coffee in forest based ecosystem of Bastar region in Chhattisgarh.